Your animal body - Gálvez, María Auxiliadora (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
This article aims to unveil the somatic gaze as a tool for questioning our modes of design. Thus emerges the animal ontology of our species, which turns out to be instrumental in changing our practices. The first part defines this gaze and then contrasts it with other ways of seeing the animal and the bodies. Throughout the process, these will provide different design strategies. The text reviews the history of western taxonomies where the human has always been separated from the rest at the top of the pyramid of life. The somatic gaze questions this distance and plunges us into understanding our composition and our imaginaries in order to reformulate them. Your animal body is the reformulation that brings with it a radical change: it is the alternative design of ourselves that brings about changes in our architectural and urban tools. We then delve into various case studies that show us ways of operating and thinking from the animal body. The final part of the article presents an agenda for architecture from this perspective and its possible application to the model of an interspecies city.
Keywords: Somatics; Interspecies city; More-than-human design; Animal body